Bilateral International Investments : The Big Sur? - Broner, Fernando; Didier, Tatiana; Schmukler, Sergio L.; von Peter, Goetz (World Bank, Washington, DC, 2021)
Using country-to-country data, this paper documents a set of novel stylized facts about the rise of the South in global finance. The paper assembles comprehensive bilateral data on cross-border bank loans and deposits, portfolio investment in debt and equity, foreign direct investment, and international reserves. The main finding is that global financial integration with and especially within the South (countries outside the G7 and Western Europe) has grown faster than within the North. By 2018, the South accounted for 24 to 40 percent of international loans and deposits, portfolio investment, and foreign direct investment, an increase of roughly 10 percentage points since 2001. The growing importance of the South is reflected in the intensive and extensive margins, with fast growth in the number of bilateral links. Although China weighs heavily in these trends, international investment in the rest of the South has increased to a similar extent.